2005
DOI: 10.1007/bf03032403
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of c-myc, c-jun and estrogen receptor in normal, hyperplastic and neoplastic endometrium

Abstract: To evaluate the role of c-jun and c-myc proto-oncogenes in normal, hyperplastic and neoplastic endometrium in relation to estrogen receptor (ER) status and to investigate whether these genes can be related to other histopathological features of endometrial carcinoma, 32 endometrial carcinomas, 38 endometrial hyperplasias and 22 cyclic endometria (10 proliferative and 12 secretory) were evaluated histologically. Endometrial hyperplasia cases were classified as simple and complex hyperplasia without atypia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 43 publications
4
30
0
2
Order By: Relevance
“…Bircan et al . showed, using immunohistochemistry, that c-jun expression occurs primarily in the proliferative phase of the menstrual cycle 80 , which was further supported by Hong et al . showing a correlation between growth in cultured endometrial stromal cells and activated c-jun expression 81 .…”
Section: Expression and Localization Of E2-erα C-fos C-jun And C-msupporting
confidence: 55%
“…Bircan et al . showed, using immunohistochemistry, that c-jun expression occurs primarily in the proliferative phase of the menstrual cycle 80 , which was further supported by Hong et al . showing a correlation between growth in cultured endometrial stromal cells and activated c-jun expression 81 .…”
Section: Expression and Localization Of E2-erα C-fos C-jun And C-msupporting
confidence: 55%
“…The decrease in ERa expression confers dual implication with regard to tamoxifentreated uterus: First, the ER-related signaling, known to mediate hyperplastic response, is diminished, and, second, the uterine response to tamoxifen is reduced because there are less tamoxifenbinding receptors per cell. c-Myc protein, known to induce proliferation and to play a role in the development of endometrial carcinoma (41), is upregulated by tamoxifen (42,43). In our mice model tamoxifen treatment causes an increase in the level of c-Myc protein, compared with its level in control mice.…”
Section: Discussionmentioning
confidence: 78%
“…The overexpression or amplification of c-Myc was observed in many types of cancers [43]. It was also proven that c-Myc could play important roles in cancer cell growth, apoptosis, metabolism, and cell differentiation [44]. Since it was demonstrated that E2 treatment could enhance the c-Myc expression in ovarian cancer cells [45], inhibition of c-Myc expression through blocking estrogen signaling may also contribute to the suppression of cancer progression.…”
Section: Discussionmentioning
confidence: 99%